Total Factor Productivity Analysis Of The Water Services Industry In Malaysia - Goh, Kim Huat (2020)
The interest in evaluating the total factor productivity of the water services industry has increased following the regulatory reform of the industry. In Malaysia, a visionary effort has been taken by the federal government on restructuring the water services industry to ensure its financial viability of water operators and to address the non-revenue water (NRW). Multitudes of initiatives as well as regulations have been introduced and implemented for the improvement of the water services industry productivity. However, there is lacking of studies conducted to assess the impact of the regulatory reform to the water services industry productivity. Therefore, the main objective of this study is to evaluate the total factor productivity (TFP) change in the water services industry in Malaysia before and after the regulatory reform. The study applies the bootstrap Malmquist Luenberger productivity index and integrates the undesirable output of NRW for the Malaysian water services industry. This study also aims to determine the drivers contributing to the TFP change in the 14 water operators before and after the regulatory reform. Moreover, this study is first attempt to capture five explanatory variables (regulatory reforms, customer density, domestic water consumption, production cost, and reserve margin) as determinants to explain the variation of productivity change in the industry. The results confirmed that during the study period, the industry experienced a deterioration in the average productivity of 0.57%, which is mainly attributed to the technical regression that occurred at an annual rate of 1.05%.